Landscape and Religious Monumentalisation in Ancient Greece: The Sanctuary of Athena Alea in Tegea - Cardete del Olmo, Mª Cruz (Gerión. Revista de Historia Antigua, 2022)
Monumentalisation is an elaborate way of building memory in and through the landscape. Taking the sanctuary of Athena Alea in Tegea as an example, this paper focuses on two constants in the relationship between monumentalisation and memory in ancient Greece. Firstly, the interaction between the two reinforced the myth of the alleged perpetuity and statism of monuments, thus contributing to make identities more resilient and inflexible and to their understanding as essentialist realities. Secondly, this interaction was used as a way of legitimising the dominant ideology, helping to naturalise it and its expressions. All this is analysed through a specific example, namely, the sanctuary of Athena Alea in Tegea.
Keywords: Monument; Mnemotopos; Greek Religion; Arkadia